The Effect of Lining Material on the Permeability of Clayey Soil - Arwa Ossama Shakir; Haifaa Abd Al-Rasool Ali (Civil Engineering Journal, 2019)
The main objectives of current work are to reduce the permeability of clayey soil for different fluid (water and crude oil) and to predict its efficiency for petroleum storage. Current research uses a sodium bentonite (B) with percentage (1.5, 3 and 6%) by the dry weight of soil and coal tar extended epoxy resin coating as the lining material. The soil sample was brought from AL -Nahrawan region. Soil's permeability for petrol was studied through using compacted soil model and making a central hole (core) in it with changing its dimensions (diameter, thickness of wall and base), type of fluid and number of filling cycles. After filling the core with these fluids, the volume losses of fluids were measured per day. When two cycles were finished, a sample was taken from the base of the core to be examined in a consolidation test. Number of laboratory tests have been conducted such as (Atterberg limits, compaction test, consolidation, sieve analysis and specific gravity).The results showed that the increase in bentonite percentage causes an increase in (optimum moisture content, Atterberg limit and specific gravity) and also decreasing in (max dry unit weight and permeability) as the fluid was water. However, an increase in permeability was obtained using the crude oil. A reduction in volume losses was observed when using the lining material, coal tar extended epoxy resin coating.